Investigational drugs for hyperuricemia, an update on recent developments. (4th May 2018) - Pascart, Tristan; Richette, Pascal
ABSTRACT: Introduction : The significant proportion of gout patients not reaching serum urate levels below 6.0 mg/dL and the debated pathogenicity of hyperuricemia (HU) itself motivate investigators to develop new drugs to decrease uricemia. Areas covered : This review discusses the drugs considered to be in active development from pre-clinical to phase III studies. This review covers 11 drugs in development, including a xanthine oxidase inhibitor (topiroxostat), uricosurics (verinurad, arhalofenate, UR-1102, tranilast), dual inhibitors (RLBN1001, KUX-1151), a uricase (pergsiticase), an inhibitor of hypoxanthine production (ulodesine), and drugs with yet-to-explain mechanisms of action (levotofisopam, tuna extracts). Expert opinion : Drugs well advanced in their development – particularly arhalofenate, verinurad and topiroxostat – open the prospect of patient-comorbidity-tailored HU management. Development of novel therapies provides new insight into our understanding of gout and HU, particularly potential pathogenicity. Apart from potency to decrease serum urate levels and good tolerance profiles, novel therapies will need to focus on administration modalities facilitating treatment adherence.